Pengembangan Media Pembelajaran Fisika Menggunakan Macromedia Flash Pro 8 Materi Gerak Lurus - Afriyanti, Mera; Sodikin, Sodikin; Jadmiko, Agus (Indonesian Journal of Science and Mathematics Education, 2018)
Abstract: This research aims to knowing the quality of feasibility of physics learning media and knowing the response of learners to the use of physics learning media using macromedia flash pro 8 straight motion materials related to the values of Al-Qur'an in class X. This research is an R and D research that adopted the development of Borg and Gall. The subjects of the study of class X students with data collection instruments used in the form of questionnaires. The results of this study are; 1) Produce product in the form of physics learning media using macromedia flash pro 8 straight motion material related to Al-Qur'an values, product quality that has been developed is very feasible with percentage of 81,11% material expert, 72,46% media expert in category worthy, 88,00% religious experts in very decent category and response of class X learner with percentage 85,92%, and 80,19% with very decent category Abstrak: Penelitian ini bertujuan untuk mengetahui kualitas kelayakan media dan mengetahui respon peserta didik terhadap penggunaan media pembelajaran fisika menggunakan macromedia flash pro 8 materi gerak lurus berkaitan nilai-nilai Al-Qur’an di kelas X. Penelitian ini merupakan penelitian R and D yang mengadopsi pengembangan dari Borg and Gall. Subjek penelitian peserta didik kelas X dengan instrumen pengumpulan data yang digunakan berupa angket. Hasil penelitian ini adalah; 1) Menghasilkan produk berupa media pembelajaran fisika menggunakan macromedia flash pro 8 materi gerak lurus berkaitan nilai-nilai Al-Qur’an, kualitas produkyang telah dikembangkan adalah sangat layak dengan persentasi 81,11 %  ahli materi, 72,46 % ahli media dalam kategori layak, 88,00 %ahli agama dalam kategori sangat layak dan respon peserta didik kelas X dengan persentase 85,92%, dan 80,19% dengan kategori sangat layak.